2020
DOI: 10.32404/rean.v7i3.5158
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Doses of Cattle Manure for Organic Chili Pepper Production

Abstract: There is a contemporary trend of change in the agricultural sector, aiming at the use of ecologically friendly inputs. This trend can be seen by the constant increase in the demand for organic products. However, as with other technologies, there is a need for studies to evaluate the effectiveness of its use. The present study aimed to evaluate the effects of the application of increasing doses of cattle manure on the development and productivity of chili peppers. The treatments consisted of increasing doses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Corroborating the results obtained in the present study, Silva et al (2019), found that the use of cattle manure together with peaty commercial substrate led to the development of pepper and sweet pepper seedlings. Also, for the pepper crop, it was found that the use of tanned cattle manure has a positive effect when used during production, increasing the development and productivity of the crop (RIBEIRO et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corroborating the results obtained in the present study, Silva et al (2019), found that the use of cattle manure together with peaty commercial substrate led to the development of pepper and sweet pepper seedlings. Also, for the pepper crop, it was found that the use of tanned cattle manure has a positive effect when used during production, increasing the development and productivity of the crop (RIBEIRO et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This demand ranges from government actions aimed at the productive sector to the demand imposed by the consumer market. In this sense, the use of organic inputs, also including waste from the agroindustry itself, has been explored, either for the production of seedlings (SILVA JÚNIOR et al, 2018;AIRES et al, 2020) or for field production (PACHECO et al, 2016;RIBEIRO et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the length and width of the leaves, there was no significant statistical variation; however, the treatment of 20% of BS limited the growth in length and 80% for the width. Therefore, the Capsicum genus was considered demanding concerning chemical characteristics of the soil (Ribeiro et al, 2020), which attributes such results to the improvement of soil characteristics caused by the application of limestone (Cardoso et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…FERNANDES (2018) concluded that radish when fertilized with organomineral fertilizer shows better growth performance. According to RIBEIRO et al (2020), the use of increasing doses, up to 20 Mg ha -1 , of cattle manure positively affects the development and productivity of chili pepper plants. Positive results were also found by PEREIRA et al (2021), showed a beneficial interaction between the bacteria (A. brasilense) and the corn plant, with an increase in the root system and chlorophyll content, in relation to the control treatment, without application.…”
Section: Discussionmentioning
confidence: 99%